Prevalent culture of online shaming amongst UiTM Law Students / Haswira Nor Mohamad Hashim...[et al.] - Mohamad Hashim, Haswira Nor; Mahmood, Anida; Suhaimi, Nurul Shuhada (Universiti Teknologi MARA, Kedah, 2018)
This paper reports the prevalent culture of online shaming amongst UiTM law students in Malaysia. A survey questionnaire was used as an instrument for data collection involving 320 UiTM law students. A cross-sectional data was collected from the survey population. The findings of the survey suggest the prevalent culture of online shaming amongst UiTM law students. The research is beneficial in raising awareness on the culture of online shaming. The survey revealed that online shaming postings are commonly found in social media application and the most prevalent anti-social behaviour associated with online shaming is on sexism, racism or religious bigotry. The survey also revealed respondents’ experience in posting or being shamed online. This paper concludes that the culture of online shaming in Malaysia is real and prevalent. This paper recommends for an awareness programme to be conducted among UiTM Law students and nationwide to emphasize on the legal implications of online shaming.